LuluDB—The Database Created Based on Small RNA, Transcriptome, and Degradome Sequencing Shows the Wide Landscape of Non-coding and Coding RNA in Yellow Lupine (Lupinus luteus L.) Flowers and Pods - Glazinska, Paulina; Kulasek, Milena; Glinkowski, Wojciech; Wysocka, Marta; Kosiński, Jan Grzegorz (Frontiers in Genetics, 2020)
Yellow lupine (Lupinus luteus L.) belongs to a legume family that benefits from symbiosis with nitrogen-fixing bacteria. Its seeds are rich in protein, that makes it a valuable food source for animals and humans. Yellow lupine is also the model plant for basic research on nodulation or abscission of organs. Nevertheless, the knowledge about the molecular regulatory mechanisms of its generative development is still incomplete. The RNA-Seq technique is becoming more prominent in high-throughput identification and expression profiling of both coding and non-coding RNA sequences. However, the huge amount of data generated with this method may discourage other scientific groups from making full use of them. To overcome this inconvenience we have created a database containing analysis-ready information about non-coding and coding L. luteus RNA sequences (LuluDB). LuluDB was created on the basis of RNA-Seq analysis of small RNA, transcriptome and degradome libraries obtained from yellow lupine cv. Taper flowers, pod walls and seeds in various stages of development, flower pedicels and pods undergoing abscission or maintained on the plant. It contains sequences of miRNAs and phased siRNAs identified in L. luteus, information about their expression in individual samples and their target sequences. LuluDB also contains identified lncRNAs and protein-coding RNA sequences with their organ expression and annotations to widely used databases like GO, KEGG, NCBI, Rfam, Pfam etc. The database also provides sequence homology search by BLAST using e.g. an unknown sequence as a query. To present the full capabilities offered by our database, we performed a case study concerning transcripts annotated as DCL 1-4 (DICER LIKE 1-4) homologues involved in small noncoding RNA biogenesis and identified miRNAs that most likely regulate DCL1 and DCL2 expression in yellow lupine. LuluDB is available at http://luluseqdb.umk.pl/basic/web/index.php.